The role of polyphenols in poultry nutrition. Issue 6 (24th September 2020) - Abdel‐Moneim, Abdel‐Moneim E.; Shehata, Abdelrazeq M.; Alzahrani, Seraj O.; Shafi, Manal E.; Mesalam, Noura M.; Taha, Ayman E.; Swelum, Ayman A.; Arif, Muhammad; Fayyaz, Muhammad; Abd El‐Hack, Mohamed E.
Abstract: In the last two decades, poultry and animal industries became increasingly interested in using plant‐based feed supplements, herbs and their derivatives to retain or enhance their health and productivity. These health benefits for the host mainly attributed to the secondary plant metabolites, namely polyphenols. Polyphenols are renowned for their antioxidant, immunomodulatory, anti‐mutagenic and anti‐inflammatory properties. However, despite these advantages of polyphenols, they have been characterized by poor absorption in the gut and low concentration in target cells that compromise their role as effective antioxidants. The low bioavailability of polyphenols necessitates the need for further investigations to harness their full potential in poultry farms. This review is existing evidence about the bioavailability of polyphenols and their antioxidant, immunomodulatory, antimicrobial, detoxification properties and their impacts on poultry performance.